Environmental Conditions of Ranchi Plateau in Early Autumn and its Effects on Potato Crop Growth - Chatterjee, B.N.; Singh, R.D.; Tewary, S.B..; Prasad, D. (Journal of Soil and Water Conservation, 2022)
The growth of any crop depends entirely on its environment. The cultivation of potato in early autumn in the Ranchi plateau area is gradually increasing. The profits made for early produce are much higher than the profits accruing during the main crop season in November-February (Mukerjee et al. 1961). Irrigation facilities are very meagre in the undulated plateau and potato planting in October-November is impossible without irrigation. The area comprising 7047 square miles of the Ranchi district lies at altitudes varying from 610 m. to 1067 m., at about 85° E and 23° N. The rainfall varies from 1250 to 1875 mm; all poured in June to September. The rain starts earlier than in neighbouring plain areas. The land surface being undulated and soil being mostly sandy loam in the uplands, the drainage is very good; this leads to low pH of the soil ranging from 4.8 to 6.5 (Mandal, 1957).